Enabling efficient hydrogen-evolution reaction over perovskite oxide electrocatalysts through phosphorus promotion. (21st September 2020) - Zhang, Zhenbao; Zhou, Wulan; Yang, Ziwei; Jiang, Jiahui; Chen, Dengjie; Shao, Zongping
Abstract: In this work, we have demonstrated that by modifying Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF) via phosphorous (P) incorporation, the hydrogen evolution reaction (HER) activity was boosted. Such P incorporation was realized through the lattice doping via an in situ method, or bulk/surface co-modification via an ex situ approach. Under optimal conditions, the derived P-doped and bulk/surface-modified BSCF exhibited η 0 of 205 and 159 mV, and η 10 of 333 and 309 mV in 1.0 M KOH, respectively. Such attractive performance resulted from multiple aspects, including the improved electrochemical active surface area, accelerated charge transfer kinetics, increased high-oxidation state of the Co cation within the Co 3+ /Co 4+ redox couple, and enlarged amount of lattice oxygen species. Moreover, the presence of amorphous regions and structure distortion of P-modified BSCF from the ex situ method greatly facilitated the HER. Graphical abstract: Image 1 Highlights: Efficient perovskite electrocatalysts were developed for HER. P-modified BSCF were prepared in situ and ex situ. P-modified BSCF exhibited η 0 of 159 mV and η 10 of 309 mV. The greatly facilitated HER originates from multiple factors.